Rekonstruksi Pembelajaran Bahasa Arab - Wulandari, Nawang (Universitas Islam Negeri Jurai Siwo Lampung, 2019)
This study aims to reformulate (reconstruct) of Arabic learning. The research site chosen is IAIN Metro Lampung. This university is one of Islamic Universities in Indonesia that requires the students to learn and master Arabic. This study formulate steps that are tailored to the characteristics of student in IAIN Metro, especially for students who are not studying at Arabic language education. After the data has been analyzed and reviewed, the conclusion of the formulation of the reconstruction of Arabic learning is to reformulate the general and specific instructional objectives, to reformulate teaching materials, learning strategies and assessment strategies.